2013
DOI: 10.1179/1743132813y.0000000268
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxLDL antibodies are clinically insignificant for stroke patients

Abstract: Patients with atherogenic ischemic stroke may have significantly higher anti-oxLDL Abs concentrations. This should be interpreted as an attempt to limit the consequences of oxLDL production; however, this phenomenon does not seem to protect patients against cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, the findings of different studies about the importance of oxLDL antibodies in association or prediction of atherosclerosis are inconsistent and inconclusive. The increased levels of anti‐oxLDL antibodies were predictive of mortality, myocardial infarction occurrence and carotid atherosclerosis progression . The autoantibodies directed against oxLDL are likely belong to two separate families of antibodies .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings of different studies about the importance of oxLDL antibodies in association or prediction of atherosclerosis are inconsistent and inconclusive. The increased levels of anti‐oxLDL antibodies were predictive of mortality, myocardial infarction occurrence and carotid atherosclerosis progression . The autoantibodies directed against oxLDL are likely belong to two separate families of antibodies .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The increased levels of anti-oxLDL antibodies were predictive of mortality, myocardial infarction occurrence and carotid atherosclerosis progression. 74 The autoantibodies directed against oxLDL are likely belong to two separate families of antibodies. 75 On one side, 'pathogenic' antibodies increase atherosclerosis progression and significantly correlate with atherosclerotic plaque formation.…”
Section: Vaccination Against Atherosclerosis?mentioning
confidence: 99%
“…In rheumatoid arthritis, IgG oxLDL‐ab levels have been demonstrated significantly higher compared with healthy controls, being strongly related to inflammation degree and the risk for atherosclerosis . Other studies have demonstrated the local production of IgG oxLDL‐ab levels in patients with aggressive periodontitis, the increased concentration in patients with atherogenic ischemic stroke, and the association with atherogenic indexes in HIV‐infected patients …”
Section: Discussionmentioning
confidence: 94%
“…28 In rheumatoid arthritis, IgG oxLDL-ab levels have been demonstrated significantly higher compared with healthy controls, 29,30 being strongly related to inflammation degree and the risk for atherosclerosis. 31 Other studies have demonstrated the local production of IgG oxLDL-ab levels in patients with aggressive periodontitis, 32 the increased concentration in patients with atherogenic ischemic stroke, 33 and the association with atherogenic indexes in HIV-infected patients. 34 Oxidized low-density lipoprotein antibodies/high-density lipoprotein cholesterol ratio was the best oxLDL-ab-based lipid index regarding all histological features, being strongly associated with NASH in lean patients.…”
Section: Discussionmentioning
confidence: 97%
“…The blood level of assessed antibodies was significantly higher in stroke patients than in control group. However, this phenomenon does not seem to protect patients against cerebrovascular events [34]. Recently a report found that a quiescent population of IgM+ plasma cells including oxLDL-specific IgM antibody secreting cells in bone marrow also sustained the elevated IgM antibody response in circulation [35].…”
Section: Discussionmentioning
confidence: 99%